Factors influencing prosocial behavior among Chinese adolescents: Empathy as a mediator - FeiFei, Teng; Jafar, Mohd Fairuz; Kasim, Marini (Edelweiss Applied Science and Technology, 2025)
This study examines the factors influencing prosocial behavior among Chinese adolescents, emphasizing empathy as a mediator within the framework of social learning theory. The research investigates how parental involvement and teacher-student relationships enhance empathy, which, in turn, fosters prosocial behavior. Data were collected through a stratified random sampling of middle schools across five regions of China, resulting in 486 valid responses measured on a 5-point Likert scale. Analysis using SPSS and SmartPLS included descriptive statistics, measurement model evaluation, and structural equation modeling. The findings reveal that both parental involvement and teacher-student relationships significantly improve empathy, positively influencing prosocial behavior. Parental involvement demonstrated a stronger effect than teacher-student relationships. The results of this study highlight the critical roles of family and school environments in promoting emotional and social development, providing insights into the mechanisms underlying adolescent prosocial behavior within the Chinese collectivist culture.